The Argumentative Dimensions of the Lexicon of Quranic Words and Expressions: A Study of Selected Models - Boudilmi, Slah Eddine (El Omda in Linguistics and Discourse Analysis, 2020)
resume In argumentative contexts, the competitors make use of infinite lexicon amplitude to strengthen their discourses, as the lexicon provides the opportunity to demonstrate the arguments logically and precisely. However, words alone are meaningless. Indeed, words earn their significance when they are contextualized and used within various structures. In the holy Quran, the used diction in fact carries lexis and terms which hold a plausible argumentative dimension, thereby affecting enormously the psychological sides of the recipients. Hence, these argumentative words and expressions are to influence the recipients so as to capitulate them to the Quranic thesis.